Probing the geometries of wormholes: A comparative study of f(R,T) and f(Q,T) theories in the presence of BEC matter - Chaitra Chooda Chalavadi; H. Aruna Kumara; V. Venkatesha (Nuclear Physics B, 2025)
This study explores wormhole solutions within two distinct modified gravity theories, namely f(R,T) gravity and f(Q,T) gravity, incorporating Bose-Einstein condensate (BEC) dark matter to analyze their geometric properties. The primary objective is to comprehensively compare wormhole characteristics in these frameworks under the influence of BEC matter. The derived shape functions satisfy all fundamental traversability conditions. Furthermore, we examine the energy conditions, revealing that the NEC holds in f(R,T) gravity but is violated in f(Q,T) gravity, highlighting the contrasting nature of wormhole solutions in these theories. Additionally, we investigate the effects of anisotropy, active gravitational mass, and surface diagram of wormhole geometries. Our findings confirm the existence of physically viable and stable wormhole models within these modified gravity theories.